How to Make a Database in Historical Studies - Gil, Tiago Luís. author. aut Link
XII, 93 p. 30 illus., 2 illus. in color.
Keywords: This book is a greatly supplemented translation from Portuguese, originally published in 2015. It discusses the most appropriate ways to create databases for research on history and other humanities, including an extensive debate about the usages that historians have made of computing since the 1950s. It has four chapters: the first is dedicated to theoretical and methodical questions about the usage of databases in history; the second is about technical issues; the third presents the concept of research engineering (how to improve research in groups); the last is about the construction of databases. The author states that the use of technology in research in history and humanities should be preceded and mediated by theories and methods which deal with these disciplines and not by technical issues. The historian must know how to think “correctly” in order to use the technological tools in an autonomous way. The book provides a background, demonstrating how theory, methodology, and technique are always articulated in historical research, and will appeal to history students and researchers.